Efficient applications of green synthesized CeO2/Bi2O3 nanocomposite for simultaneous electrochemical determination of Pb (II) and Cd (II) in real samples - Hadi Mahmoudi-Moghaddam; Sahar Zinatloo-Ajabshir; Saeid Ahmadzadeh; Ali Azari (Scientific Reports)
Abstract In this study, Bi2O3/CeO2 nanocomposite was synthesized using serine, which played a dual role by promoting uniform particle morphology and aiding combustion during synthesis, resulting in a highly porous nanostructure. The produced nanocomposite was applied as a highly efficient modifier for screen-printed electrode (Bi2O3/CeO2/SPE), facilitating the simultaneous quantification of Pb(II) and Cd(II) using square wave anodic stripping voltammetry (SWASV). Compared to conventional sensors, the proposed electrode exhibited significantly enhanced electrochemical behavior, attributed to the synergistic structural and electrical properties of CeO₂ and Bi₂O₃ as well as an increased surface area. The sensor demonstrated a reliable response and effective peak separation at optimal parameters. The current signals exhibited linearity within the concentration range between 0.5 and 85 µg/L for both ions, achieving the limit of detection (LOD) of 0.09 µg/L for Pb(II) and 0.14 µg/L for Cd(II). The Bi2O3/CeO2/SPE was effectively utilized to detect cadmium and lead ions in water and food samples, demonstrating high recovery values across different spiked samples, and the outcomes closely matched those obtained through standard ICP analysis.